Effect of Temperature on the Photobehavior of Rose Bengal Associated with Dipalmitoylphosphatidyl Choline Liposomes - Lissi-Gervaso, E; Abuin-Saccomano, E (2011)
The association and photobehavior of Rose Bengal (RB) in the presence of dipalmitoylphosphatidyl choline (DPPC) small unilamellar liposomes is determined by the temperature. At temperatures above the main phase transition of the bilayer, the incorporation of the dye is ca. 2.5 times more efficient than that taking place when the bilayer is in the gel state. In both temperature ranges, adsorption isotherms show a noticeable anti-cooperativity that can be related to electrostatic repulsion between bound molecules. The photophysics and the photochemistry of the bound dye molecules also depend on the bilayer status. In particular, in the liquid crystalline state the surrounding of the dye is more polar and production of singlet oxygen is less efficient (??0.1). This reduced singlet oxygen production is partially due to a low triplet yield (?T=0.35) and triplet self-quenching due to a high local RB concentration. In spite of these, tryptophan is efficiently photobleached when RB is associated to liposomes in the liquid crystalline state, probably due to a Type I mechanism favored by its high local concentration in the sensitized surroundings. © 2011 Elsevier B.V. All rights reserved.